Accounting for capital increase in companies - arioua, Rachid (Journal of Research in Finance and Accounting, 2025)
This study addresses a topic in accounting and finance, which is the accounting for capital increase in companies, especially financial companies, due to their unique characteristics prescribed by commercial law, particularly the principle of fairness among partners. It also discusses the methods of capital increase, as well as the nature and content of the special report prepared by the accounts manager for amending the articles of association. The study concludes that in order to increase capital, it is necessary to first prepare a capital increase project, then determine the issuance price based on whether there is public resort to savings or not. It also emphasizes the importance of calculating the fair value and determining the rights of bonus shares and subscription rights to achieve the principle of fairness among partners. Additionally, it discusses the accounting treatment in accordance with the financial accounting system.